Pragmantisme Politik: Studi Kasus Proses Rekrutmen Politik PDO-P Pada Pilkada Kabupaten Sleman - MAHADI, HELMI (Jurnal Studi Pemerintahan, 2011)
This research will explains on candidate recruitment of major in Sleman that conducted by PDI-P andtheir behavior. This research uses a case study method through in-depth interviews and writtendocumentation. The result shows that the failure of PDI-P Sleman in carrying internal candidate fromthe party is due to the occurrence of political pragmatism. In this context, pragmatism comes from twothings. Firstly, internal factor is the failure of the PDI-P cadre of Sleman and the phenomenon ofmoney as a determinant of recruitment of candidates. Secondly, external factor is the political cultureof society that do not directly influence through elite perceptions about public preferences.Keywords: Political recruitment, party’s pragmatism, and society’s pragmatism